2005
DOI: 10.1191/0267659105pf793oa
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokine inhibition of erythropoiesis in patients implanted with a mechanical circulatory assist device

Abstract: Mechanical circulatory assist devices (MCADs) are increasingly utilized independently of cardiac transplantation in the management of heart failure. Though MCAD use incorporates inherent mechanical risks, the inevitable onset of chronic anemia, with its associated morbidity and mortality, is also a significant concern. MCAD support has been correlated with elevated plasma levels of inflammatory cytokines TNF-alpha, IL-1beta, and IL-6, which have separately been found to inhibit erythropoietin (Epo)-induced ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
232
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(249 citation statements)
references
References 24 publications
6
232
0
4
Order By: Relevance
“…Inflammatory cytokines and neurohumoral mediators are activated in acute and chronic cardiovascular diseases. Inflammatory cytokines have been found to suppress the maturation of erythrocytes, and the increased immature erythrocytes may therefore reflect higher RDW levels (15). Admission RDW (aRDW) has recently been shown to predict mortality in trauma patients by an unclear mechanism (14).…”
Section: █ Resultsmentioning
confidence: 99%
“…Inflammatory cytokines and neurohumoral mediators are activated in acute and chronic cardiovascular diseases. Inflammatory cytokines have been found to suppress the maturation of erythrocytes, and the increased immature erythrocytes may therefore reflect higher RDW levels (15). Admission RDW (aRDW) has recently been shown to predict mortality in trauma patients by an unclear mechanism (14).…”
Section: █ Resultsmentioning
confidence: 99%
“…Possible contribution of inflammation to anisocytosis results from inhibition of the response production against erythropoietin, impaired iron metabolism, and shortened time of red blood cell survival [19]. In addition, it has been found in previous studies that inflammatory cytokines suppress the maturation of erythrocytes, therefore immature erythrocytes which enter the circulation may accelerate erythropoiesis [20]. Previously, we published first outcomes of this study and demonstrated that there was a good correlation between hs-CRP level, which is an important inflammatory marker and RDW level on admission [21].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is the increased levels of inflammatory cytokines having impacts on iron metabolism and bone marrow function (11,12). RDW is related to the proliferative responses of erythropoiesis and will rise in similar fashion with the reticulocyte count during increased production of immature RBCs (16). In a recent study (17), Gotsman et al have shown that TNF-α and IL-6 levels are related to Gensini score.…”
Section: Discussionmentioning
confidence: 99%